A reflection on the policy of culling brown bears (Ursus arctos) in Romania - Quintanilha, Tiago Lima (Zenodo, 2021)
In this article, we present a critical reflection on the policy of culling brown bear ( Ursus arctos ) populations in Romania, to understand how these policies can be adjusted by introducing complementary analyses of the (neglected) impact of anthropogenic effects upon bear habitats. In particular, we focus on human-driven deforestation and its effects on increasing conflicts between bears and human settlements, as well as the use of unrealistic bear population estimates to legitimize larger hunting quotas for economic purposes. We use studies on the impact of human activity upon the habitats of different sub-species of bears to demonstrate that human interference in bear habitats is not only responsible for massive deforestation in Romania, but also leads to an increase in human-bear conflicts in the country. Thereby, we attempt to demonstrate that brown bear culling policies in Romania, which tend to legitimize, tacitly, the demonization of bear populations, are unfounded according to multiple studies and can be replaced by alternative models to manage human-bear conflicts.